Lexical Tradition and Novelty in a Coastal Area (Bío-Bío) and Araucania Regions (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
This paper presents the conclusions of a dialectological research developed in a coastal area in the south of Chile (Bío-Bío and Araucania Regions). The analysis of the material shows remarkable traditional lexical stability derived from Hispanic roots related to navigation and small fishing vessels. More changes and geographical variations are observed with respect to the fishing terminology as a result of the changes in that referential domain during the last decades. Some indigenous terms from Mapudungun, language that has lost much vitality in this area of the country, are also recognized in this study.
Keywords: Traditional terminology; Geographical or Dialectological variation; Lexical innovation; Indigenous terminology